Habitual Snoring in Children with Previous Allergic Sensitization. (April 2013) - Zicari, A.M.; Occasi, F.; Marcelli, A. Cesoni; Lollobrigida, V.; Celani, C.; Indinnimeo, L.; Tancredi, G.; De Castro, G.; Duse, M.
Previous studies have reported a high prevalence of allergy in children with Habitual Snoring (HS), but the relationship between allergy in the early years of life and the subsequent development of this Sleep Disordered Breathing (SDB) is yet to be elucidated. The purpose of the present study was to determine the role of early, under 36 months of age, allergic sensitization to food (with or without sensitization to airborne allergens) in determining the development of HS 8–10 years after. One hundred and fortyeight children (10–14 years, mean age 12 years) with a history of food allergy were selected. Under the age of 36 months, atopic status was assessed by skin prick test for a panel of airborne and food allergens. Questionnaires filled in by parents were used to collect information on children's snoring and associated symptoms. HS was defined as snoring three or more times per week. At 1–3 years of age 54 (36.5%) children were positive to food allergens alone, and 94 (63.5%) were positive also to airborne allergens. After 8–10 years of life, when patients were aged between 10 and 14 years, habitual snoring was reported in 37 (25%) children. Furthermore, among the 54 children under three years of age sensitized only to food, 8 (14.8%) became HS while of the 94 children sensitized to both food and inhalants allergens 29 (30.9%) developed HS. The difference between those two groups was statistically significant (p=0.04). We reported a significant risk of developing HS in children with early allergic sensitization. Specifically this risk was higher when food allergy was associated with inhalant allergy. The onset of upper airway inflammation due to allergic triggers in subjects under three years of age may be related to the subsequent development of SDB after 8–10 years.